Abstract 15 — Lupus Low Disease Activity State: An Underutilised Clinical Target that is Attainable and Protective against Lupus Nephritis Relapse - Chak Kwan Cheung; Chak Sing Lau; Shirley Chiu Wai Chan (Journal of Clinical Rheumatology and Immunology, 2023)
Background Lupus nephritis (LN) is a significant comorbidity affecting approximately 50-60% of patients with systemic lupus erythematosus (SLE). Complete and partial renal response (CRR/PRR) have been recommended as treatment targets in LN. Lupus low disease activity state (LLDAS) is also associated with favourable clinical outcomes. This study aims to investigate the LLDAS attainment rate and outcomes in patients with LN. Methods Patients with biopsy-proven LN during 2010-2020 in Queen Mary Hospital were included. Baseline demographics, blood parameters and urinalysis results were documented. Renal response and LLDAS attainment were assessed at 12 months after LN diagnosis. CRR was defined as proteinuria [Formula: see text]0.5g/day with a normal estimated glomerular filtration rate (eGFR); PRR was defined as a reduction in proteinuria by [Formula: see text]50% with near normal eGFR. A relapse was defined as a biopsy-proven active LN on histology after an initial treatment response of proteinuria reduction of [Formula: see text]50% or to sub-nephrotic range. Time-to-relapse survival analysis was performed to compare the significance of CRR/PRR and LLDAS attainment. Results 143 LN patients were included, with a median follow-up duration of 10.4 years. At 12 months, 57 (40%), 14 (10%) and 69 (48%) patients achieved CRR, PRR and LLDAS, respectively. Although 39 (27%) patients attained both CRR/PRR and LLDAS, a significant number of 30 (21%) patients reached LLDAS without meeting CRR/PRR (Figure 1). Among 136 patients who achieved the pre-defined treatment response, 30 (22%) patients developed LN relapse after a median of 2.98 years. Patients reaching either CRR/PRR or LLDAS had a significantly lower risk of relapse (CRR/PRR: HR = 0.34, p = 0.02; LLDAS: HR = 0.28, p = 0.003). The attainment of both CRR/PRR and LLDAS was associated with the lowest risk of relapse (Figure 2). Conclusion We advocate LLDAS as a target for LN patients as attaining LLDAS reduces future LN relapse risks.